Shallow drainage of agricultural peatlands without land-use change: have your peat and eat it too - Heuts, T. S.; Giersbergen, Q. van; Nouta, R.; Nijman, T. P. A.; Aben, R. C. H.; Scheer, O. van der; Heuts, P. G. M.; Skovsholt, L. J.; Quadra, G. R.; Smolders, A. J. P.; Fritz, C. (Frontiers in Environmental Science, 2024)
Drainage for agricultural purposes is one of the main drivers of peatland degradation, leading to significant greenhouse gas (GHG) emissions, biodiversity loss, and soil eutrophication. Rewetting is a potential solution to restore peatlands, but it generally requires a land-use shift to paludiculture or nature areas. This study explored whether three different water level management techniques (subsoil irrigation, furrow irrigation, and dynamic ditch water level regulation) could be implemented on dairy grasslands to yield increases in essential ecosystem services (vegetation diversity and soil biogeochemistry) without the need to change the current land use or intensity.We investigated vegetation diversity, soil biogeochemistry, and CO2 emission reduction in fourteen agricultural livestock pastures on drained peat soils in Friesland (the Netherlands). Across all pastures, Shannon-Wiener diversity was below 1, and the species richness was below 5. The plant-available phosphorus (P) was consistently higher than 3 mmol L -1 . None of the water level management (WLM) techniques enhanced vegetation diversity or changed soil biogeochemistry despite a notable increase in water table levels. The potential for CO2 emission reduction remained small or even absent.Indicators of land-use intensity (i.e., grass harvest and fertilization intensity), however, showed a strong negative correlation with vegetation diversity. Furthermore, all sites' total and plant-available P and nitrate exceeded the upper threshold for species-rich grassland communities.In conclusion, our research suggests that incomplete rewetting (i.e., higher water tables while maintaining drainage) while continuing the current land use does neither effectively mitigate GHG emissions nor benefit vegetation diversity. Therefore, we conclude that combining WLM and reducing land-use intensity is essential to limit the degradation of peat soils and restore more biodiverse vegetation.